Optimalisasi Media Sosial Sebagai Sarana Personal Branding Positif dan Kreativitas Digital - Bumi, Muhammad Restu; Juantito, Aria; Aulia, Sulton; Barokah, Akbar; Wijaya, M. Habibullah (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyse the role of personal branding and identify effective strategies for managing it on social media in the digital age. The study uses a qualitative approach with data collection techniques in the form of in-depth interviews with individuals who are considered successful in consistently building and maintaining their personal branding across various social media platforms. The data obtained was analysed thematically to find patterns, strategies, and key factors that contribute to the success of personal branding. The results of the study show that consistency in conveying one's identity, authenticity in displaying personal values and character, and active interaction with the audience are the main factors in strengthening personal branding. In addition, the presentation of content that is relevant, valuable, and tailored to the needs of the audience plays an important role in maintaining engagement and expanding the reach of personal brands. These findings confirm that planned and sustainable personal branding management on social media contributes significantly to the existence and success of individuals in the digital space